Words from the Background and Degrees of Danger: the Nietzsche’s Philosophy in Los siete locos [The Seven Madmen]and Los Lanzallamas[The Flamethrowers]by Roberto Arlt - Niño Arteaga, Yesid (Universidad Pedagógica y Tecnológica de Colombia, 2019)
this article reflect on the budget that the Argentine writer Roberto Arlt was a persistent reader of the philosophy of the German Friedrich Nietzsche and that his novel work what establishes a deep relationship with the thought of the tragic that is characteristic of Nietzsche's philosophical thought. In this way the article reflects on the permeability and contaminations present in the novels Los siete locos and Los lanzallamas researching into the creative and literary opportunities of his narrative form and the images of language. Finally, the article study why the fiction of Roberto Arlt is conceived under the influence of Nietzsche's philosophical thought such as the possibility of transgression, aggression in language, transvaluation and the relations of forces, which permeate the meaning of the tragic and the non-genius contained in this novels of Roberto Arlt.